Distributed Collaborative Optimization of New Energy Stations and Energy Storage Power Stations Taking Account of the Uncertainty of New Energy - WU Xiaogang; WU Xinhua; JI Qingfeng; MA Mingyu; LIGAO Junjie (Zhejiang dianli, 2022)
New energy stations and energy storage power stations are working in closer cooperation in the context of a high proportion of new energy access with high uncertainty. Given the characteristics of distributed autonomous decision-making between new energy stations and energy storage power stations， a decomposition collaborative mechanism based on the alternating direction method of multipliers （ADMM） is used to establish a distributed collaborative optimization model of two operators considering the uncertainty of new energy. The optimal energy storage charging and discharging strategy under the distributed framework is obtained through few information iterations. The effectiveness and applicability of the proposed algorithm are verified by comparing the computational results of the proposed algorithm with those of the centralized algorithm using data from a small integrated energy system in North China.